Status of soil organic matter in paddy fields in Taratara Satu village, West Tomohon District Tomohon City - Temongmere, Caecilia Diana; Soputan, Ronny; Kumolontang, Wiesje J. N. (Soil and Environment Journal, 2024)
This study aimed to determine the status of soil organic matter in rice paddy fields in Taratara Satu village, West Tomohon District, Tomohon City. This research method with soil sampling techniques by Composite Sampling, and then the samples are analyzed C-organic using the method (Walkey and Black). Based on the result of this study, the results of chemical analysis of medium N, medium F, medium K, early organic C-organic, fields soil pH ranging from 5.2-5.7 with slightly acidic criteria and soil physical properties are clay rice soil texture with 35% sand content, 20% dust, and 40% clay. The content of organic matter is classified as medium both with puddle height of 1 cm and 10 cm. Keywords: Rice Field, Organic Matter, C-organic Abstrak Tujuan penelitian ini untuk mengetahui status bahan organik tanah pada lahan padi sawah di Kelurahan Taratara Satu Kecamatan Tomohon Barat Kota Tomohon. Metode penelitian ini menggunakan metode survei lapang dengan teknik pengambilan sampel tanah secara Composite sampling, kemudian sampel dianalisis C-organik menggunakan metode (Walkey and Black). Berdasarkan hasil penelitian ini hasil analisis kimia N sedang, F sedang, K sedang, C-organik awal sedang, pH tanah lapang berkisar 5,2-5,7 dengan kriteria agak masam dan sifat fisik tanahnya dengan tekstur tanah sawah adalah liat dengan kandungan pasir 35%, debu 20%, dan liat 45%. Kandungan bahan organik tergolong sedang baik dengan tinggi genangan 1 cm maupun 10 cm Kata kunci: Tanah Sawah, Bahan Organik, C-organik